Then and Now: Sleep Tight (The Biblical archaeology review, 2024)
The average person spends about a third of their life asleep. Those over 67 sleep more than anyone else, and those with no children (perhaps not surprisingly) sleep more than those with. Although some of that sleep happens in unusual places—like airplanes, cars, and theaters—most of it happens in a bed. Humans have been making […]